Cumplimiento sin Cumplimiento. La UIF–Perú incorporada a la SBS, oficial sin autonomía, la función a dedicación no exclusiva: una ventana hacia el lavado de activos - Puémape Postigo, Daniel Ángel (2021)
In this article, the author points out the legal deficiencies of the money laundering prevention system: the regulatory deficiencies and competence of the regulatory entities that have contributed to the imperfection to strengthen the prevention system, the little functional autonomy of the UIF-Peru incorporated to the SBS in the role of its functions, the non-exclusive dedication and lack of autonomy of the compliance officer, the lack of prevention and control willingness of shareholders and managers ready to assume risks and criminal consequences in the organization, and the confidentiality of reserved reports are some of the deficiencies towards a money laundering window.